2016
DOI: 10.15740/has/au/11.2/96-103
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of technical and allocative efficiency of brinjal farm in Bilaspur district of Chhattisgarh

Abstract: The study investigated the technical efficiency and allocative efficiency of brinjal farm in Bilaspir district of Chhattisgarh, using a stochastic frontier production function. Pre-tested questionnaires were used to collect the primary data from 154 randomly selected respondents. The study revealed return to scale on brinjal farm positive and less than unity as 0.58 which indicated that brinjal production in stage two of the production surface. The stochastic frontier analysis showed that 22.3 per cent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The score pointed out that the cauliflower growers could reduce the current cost of the produce by 59.00% achieved a potential minimum cost of production relative to the efficient farmers given current level of output. The findings are in line with the findings of the study conducted in Bilaspur district of Chhattisgarh to assess the technical and allocative efficiency of brinjal farms by Tegar et al, 14 Holding size wise examination of the score of CE indicated that marginal farmers, small farmers, medium farmers and large farmers would be wiser in reducing the current cost of the produce by 59.00%, 60.00%, 65.00% and 51.00% respectively, to achieve the potential minimum cost of production relative to the efficient farmers given current output level.…”
Section: Resource Use Efficiency Of Cauliflower Productionsupporting
confidence: 90%
“…The score pointed out that the cauliflower growers could reduce the current cost of the produce by 59.00% achieved a potential minimum cost of production relative to the efficient farmers given current level of output. The findings are in line with the findings of the study conducted in Bilaspur district of Chhattisgarh to assess the technical and allocative efficiency of brinjal farms by Tegar et al, 14 Holding size wise examination of the score of CE indicated that marginal farmers, small farmers, medium farmers and large farmers would be wiser in reducing the current cost of the produce by 59.00%, 60.00%, 65.00% and 51.00% respectively, to achieve the potential minimum cost of production relative to the efficient farmers given current output level.…”
Section: Resource Use Efficiency Of Cauliflower Productionsupporting
confidence: 90%
“…The river bed farming is also a common practice by people (especially in dry seasons from October to May) for growing vegetables like cauliflower, cabbage, chilli, brinjal, cucumber, spinach, potato, tomato, onion, pumpkin etc. (Beck et al, 2015;Tegar et al, 2016).…”
Section: Agricultural Activities and Runoffmentioning
confidence: 99%